On the rational second kind Chebyshev pseudospectral method for the solution of the Thomas–Fermi equation over an infinite interval - Kilicman, Adem; Hashim, Ishak; Kajain, Majid Tavassoli; Maleki, Mohammad (Elsevier BV, 2014)
In this paper, we propose a pseudospectral method for solving the Thomas–Fermi equation which is a nonlinear singular ordinary differential equation on a semi-infinite interval. This approach is based on the rational second kind Chebyshev pseudospectral method that is indeed a combination of tau and collocation methods. This method reduces the solution of this problem to the solution of a system of algebraic equations. The slope at origin is provided with high accuracy. Comparison with some numerical solutions shows that the present solution is effective and highly accurate.